2004
DOI: 10.1002/macp.200300235
|View full text |Cite
|
Sign up to set email alerts
|

Inversion of Phase Morphology in Polymer‐Blend Thin Films on Glass Substrates

Abstract: Summary: The phase‐morphology inversion in two blend systems of polystyrene/poly(methyl methacrylate) (PS/PMMA) and polystyrene/poly(ε‐caprolactone) (PS/PCL) has been studied after their thin films were prepared on glass substrates by spin‐coating from a co‐solvent tetrahydrofuran (THF). Phase‐contrast microscopy (PCM), scanning‐electron microscopy (SEM) equipped with energy dispersive X‐ray spectroscopy (EDS), and atomic force microscopy (AFM) were used to obtain information on the morphology of the thin film… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 39 publications
(36 reference statements)
4
22
0
Order By: Relevance
“…The effect of molecular weight on the blends' gradient structure is reflected by the relation of the molecular weight and polymer viscosity 37. Zong et al38 studied the influence of component viscosity on the development of phase morphology by blending the different molecular weight of polystyrene (PS) and poly(ε‐caprolactone) (PCL), and found that the lamella structure of compound developed slower with increasing viscosity of PS. The movement and diffusion of molecular chain become difficulty with increasing molecular weight of polymer.…”
Section: Resultsmentioning
confidence: 95%
“…The effect of molecular weight on the blends' gradient structure is reflected by the relation of the molecular weight and polymer viscosity 37. Zong et al38 studied the influence of component viscosity on the development of phase morphology by blending the different molecular weight of polystyrene (PS) and poly(ε‐caprolactone) (PCL), and found that the lamella structure of compound developed slower with increasing viscosity of PS. The movement and diffusion of molecular chain become difficulty with increasing molecular weight of polymer.…”
Section: Resultsmentioning
confidence: 95%
“…It can be suggested that in the initial stages of the phase inversion process, fast precipitation of the PS occurs. PS separates from PMMA and solidifies as a PS-rich phase, while the PMMA phase collapses below the PS-air interface [43]. In the later immersing stage, increase in the water inflow results in a secondary polymer-rich/polymer-lean phase separation [44].…”
Section: Fabrication and Characterization Of Polystyrene-based Membranementioning
confidence: 99%
“…Just as the magnitudes of surface interactions between polymer components and between the polymers and the substrate are principle considerations in morphology development, the surface area of interaction is equally important. Experimentally, the interfacial area between blend components is determined by blend composition through its influence on domain sizes [2,41,49,50]. To study and quantify the blend compositions where nano-rose formation is possible, film thickness gradients of 45 kDa PCL/SIS vector 4293A blends with compositions ranging from pure PCL (0% SIS) to pure SIS (100% SIS) were flow coated from toluene.…”
Section: Effect Of Blend Composition On Morphologymentioning
confidence: 99%